2019
DOI: 10.1016/j.stem.2019.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Complex Oscillatory Waves Emerging from Cortical Organoids Model Early Human Brain Network Development

Abstract: Highlights d Long-term, single-cell transcriptomics reveals cortical organoid developmental dynamics d Cortical organoids exhibit phase-amplitude coupling during network-synchronous events d Differential role of glutamate and GABA in initiating and maintaining oscillations d Network-level events are similar to the human preterm neonatal EEG features

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
618
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 618 publications
(722 citation statements)
references
References 63 publications
50
618
2
1
Order By: Relevance
“…Collectively, these experiments demonstrate the existence of highly sophisticated physiological activities within Cx+GE organoids, congruent with their cytoarchitectural and cellular complexity. These results stand in agreement with findings recently reported by Trujillo et al, who have also observed the emergence of neural oscillations in cortical organoids cultured for prolonged time periods using a different recording approach 40 . Our studies here further demonstrate that the emergence of higher order network activities such as multi-frequency oscillations requires functional integration of inhibitory interneurons into the excitatory network framework as permitted by the organoid fusion technique, since no oscillations were apparent without them.…”
Section: Discussionsupporting
confidence: 94%
“…Collectively, these experiments demonstrate the existence of highly sophisticated physiological activities within Cx+GE organoids, congruent with their cytoarchitectural and cellular complexity. These results stand in agreement with findings recently reported by Trujillo et al, who have also observed the emergence of neural oscillations in cortical organoids cultured for prolonged time periods using a different recording approach 40 . Our studies here further demonstrate that the emergence of higher order network activities such as multi-frequency oscillations requires functional integration of inhibitory interneurons into the excitatory network framework as permitted by the organoid fusion technique, since no oscillations were apparent without them.…”
Section: Discussionsupporting
confidence: 94%
“…The estimated connectivity ( Figure 5) combined with quantitative analyses, such as graph-theory approaches ( Figure 6), enabled us to describe the developmental progress of the cultures, thus demonstrating the capability of detecting basic neuronal features such as the increased synaptic connectivity and the formation of few, highly connected network hubs. These latter are both indexes of more mature neuronal circuits and agree well with higher spiking frequencies and network burst generation observed in mature neuronal cultures [63].…”
Section: Discussionsupporting
confidence: 84%
“…4F), consistent with the role of microglia in synaptic remodeling (49,50). In addition, we explored whether presence of microglia might influence functional network maturation that is known to occur in organoids (51). We recorded spontaneous neural activity using multi-electrode arrays in neuroimmune and control organoids at 5 weeks after transplantation and found increased synchronization and frequency of oscillatory bursts in neuroimmune organoids compared to control ( Fig.…”
Section: Introductionsupporting
confidence: 65%